Electrochemical oxidation of tramadol in low-salinity reverse osmosis concentrates using boron-doped diamond anodes. (1st April 2015) - Lütke Eversloh, Christian; Schulz, Manoj; Wagner, Manfred; Ternes, Thomas A.
Abstract: The electrochemical treatment of low-salinity reverse osmosis (RO) concentrates was investigated using tramadol (100 μM) as a model substance for persistent organic contaminants. Galvanostatic degradation experiments using boron-doped diamond electrodes at different applied currents were conducted in RO concentrates as well as in ultra-pure water containing either sodium chloride or sodium sulfate. Kinetic investigations revealed a significant influence of in-situ generated active chlorine besides direct anodic oxidation. Therefore, tramadol concentrations decreased more rapidly at elevated chloride content. Nevertheless, reduction of total organic carbon (TOC) was found to be comparatively low, demonstrating that transformation rather than mineralization was taking place. Early stage product formation could be attributed to both direct and indirect processes, including demethylation, hydroxylation, dehydration, oxidative aromatic ring cleavage and halogenation reactions. The latter led to various halogenated derivatives and resulted in AOX (adsorbable organic halogens) formation in the lower mg/L-range depending on the treatment conditions. Characterisation of transformation products (TPs) was achieved via MS n experiments and additional NMR measurements. Based on identification and quantification of the main TPs in different matrices and on additional potentiostatic electrolysis, a transformation pathway was proposed. Graphical abstract: Highlights: Galvanostatic electrochemical transformation of tramadol in reverse osmosis brines. Identification of transformation products during electrochemical treatment. Elucidation of the transformation pathway.